The Influence of Financial Literacy, Lifestyle, and Social Environment on the Family Financial Planning Behavior in Rambangaru Village, Waingapu City, East Sumba (NTT) (Case Study of PKK Women of Rambangaru Village - Ricko Fredrik Rihi; Elly Lestari; Fendiyatmi Kusufa (International Journal of Management and Business, 2025)
The purpose of this study is to determine the influence of financial literacy, lifestyle and social environment on financial planning behavior in families in Rambangaru Village, Waingapu City, East Sumba (NTT) partially and simultaneously. This study uses a quantitative method. The sample was determined by stratified random sampling technique so that the research sample was 35 families in Rambangaru Village, Waingapu City, East Sumba (NTT). The data collection technique used by the researcher is a questionnaire. The data analysis method used is multiple linear regression using the SPSS 25 program. The results of the study prove that financial literacy has a significant effect on financial planning behavior with a t-value of 4,039, lifestyle has a significant effect on financial planning behavior with a t-value of 4,134 and social environment has a significant effect on financial planning behavior with a t-value of 4,078. The results were simultaneously known that financial literacy, lifestyle and social environment had a significant effect on financial planning behavior with a value of Fcal (12,013) or 53,8%. The results of this study can be understood that the existence of good financial literacy, lifestyle control skills and a good social environment are able to support family financial planning behavior.